2022
DOI: 10.1016/j.ejca.2021.11.015
|View full text |Cite
|
Sign up to set email alerts
|

T cell immune awakening in response to immunotherapy is age-dependent

Abstract: treatment (T0) and after the first cycle of treatment at week 3 (W3). Results: We observed a correlation between T IE abundance and age at T0 (r Z 0.40), which reduced following treatment at W3 (r Z 0.07). However, at W3, we observed two significantly opposing patterns (p Z 0.03) of TCR repertoire rearrangement in patients who responded to treatment, with patients !70 years of age showing an increase in TCR clonality and patients <70 years of age showing an increase in TCR diversity. Conclusions: We demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Knowledge about multiple clinical variables is essential for precision immune-oncology and clinical decision making. By examining the clinical characteristics of patients with melanoma treated with first-line anti-PD-1 mAb, Zena et al observed age-related effects on TCR repertoire evolution and T IE cell expansion, showing that age influences T-cell reinvigoration by ICI therapy and, therefore, that it should be included among the biomarkers used to monitor responses to immunotherapy [ 105 ]. Additional research suggested that T-cell clones shared between blood and tumor (overlapping clones) are those more informative on the clinical outcome, as a higher frequency of overlapping clones within peripheral CD8 + T cells before anti-PD-1 treatment was associated with a favorable clinical response [ 106 108 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about multiple clinical variables is essential for precision immune-oncology and clinical decision making. By examining the clinical characteristics of patients with melanoma treated with first-line anti-PD-1 mAb, Zena et al observed age-related effects on TCR repertoire evolution and T IE cell expansion, showing that age influences T-cell reinvigoration by ICI therapy and, therefore, that it should be included among the biomarkers used to monitor responses to immunotherapy [ 105 ]. Additional research suggested that T-cell clones shared between blood and tumor (overlapping clones) are those more informative on the clinical outcome, as a higher frequency of overlapping clones within peripheral CD8 + T cells before anti-PD-1 treatment was associated with a favorable clinical response [ 106 108 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the epidemiologic characteristics and clinical treatments of GBM exacerbated systemic immunosuppression. First, the median age diagnosis of GBM is 64 years, and patients are mainly composed of elderly patients with age-related immunosuppression, whose immunity are significantly weaker than that of younger patients, and whose bone marrow and thymus produce significant fewer T cells [23][24][25][26] ; Second, standard-of-care can cause iatrogenic immunosuppression and lead to systemic lymphopenia, termed treatmentrelated lymphopenia 7,27,28 ; Third, dexamethasone, the most often used to alleviate brain edema in GBM patients, also induces systemic depletion of naïve and memory T cells but increases immunosuppressive myeloid cells 29 . The prevailing immune-modulating therapies mainly focus on remodeling TME, aiming to overcome local immunosuppression to promote effector T cells infiltration and reinforce immune response against tumor 30 .…”
mentioning
confidence: 99%
“…So, downregulating these kinds of checkpoints could activate T cells to have stronger anti-cancer capacities. [ 16 ] PD-1 had recently been an important and hopeful checkpoint. PD-1 inhibitor-nivolumab played a significant role in anticarcinogenic actions, which had been proved by several phase II to III clinical trials.…”
Section: Discussionmentioning
confidence: 99%